2017
DOI: 10.1038/ni.3766
|View full text |Cite
|
Sign up to set email alerts
|

The A946T variant of the RNA sensor IFIH1 mediates an interferon program that limits viral infection but increases the risk for autoimmunity

Abstract: The single nucleotide polymorphism, rs1990760, in the cytosolic viral sensor, IFIH1, results in an amino-acid change (p.A946T) and is associated with multiple autoimmune diseases. The impact of this polymorphism on both viral-sensing and autoimmune pathogenesis remains poorly understood. Here, we find that human PBMCs and cell lines with the risk variant, IFIH1T946, exhibit heightened, basal and ligand-triggered type I interferon (IFN-I) production. Consistent with these findings, IFIH1T946 knock-in mice displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 59 publications
6
119
1
Order By: Relevance
“…We also identified a novel association of the IFIH1 loss-of-function allele rs1990760-C (p.T946A) with risk of asthma. The rs1990760-C allele, which protects against autoimmune diseases and increases risk of ulcerative colitis, has been shown to decrease interferon (IFN) signaling and lower resistance to viral challenge 40 , while complete loss-of IFIH1 function makes children susceptible to severe viral respiratory infections 41,42 . The association of rs1990760-C with increased risk of asthma discovered in our meta-PheWAS is consistent with the observation that bronchial epithelial cells from asthmatics produce lower amounts of IFN-β during viral infections 43 , a finding that lead to inhaled IFN-β being tested in phase 2 clinical trials for the treatment of virus-induced asthma exacerbation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We also identified a novel association of the IFIH1 loss-of-function allele rs1990760-C (p.T946A) with risk of asthma. The rs1990760-C allele, which protects against autoimmune diseases and increases risk of ulcerative colitis, has been shown to decrease interferon (IFN) signaling and lower resistance to viral challenge 40 , while complete loss-of IFIH1 function makes children susceptible to severe viral respiratory infections 41,42 . The association of rs1990760-C with increased risk of asthma discovered in our meta-PheWAS is consistent with the observation that bronchial epithelial cells from asthmatics produce lower amounts of IFN-β during viral infections 43 , a finding that lead to inhaled IFN-β being tested in phase 2 clinical trials for the treatment of virus-induced asthma exacerbation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Among all these mutations, the gain-of-function missense mutation A946T in IFIH1 (rs1990760) has been confirmed to be associated with T1DM as well as several other autoimmune diseases in several independent studies (57-59). IFIH1 A946T confers increased basal and ligand-triggered type 1 IFN expression, and transgenic mice with the A946T risk allele exhibit increased basal type 1 IFN expression (60). Additionally, several studies showed that the IFIH1 A946T risk allele exerts its effect via the IFNβ-mediated response rather than through IFN-α, and IFN-β can promote persistent LCMV (lymphocytic choriomeningitis virus) infection, which causes enduring beta-cell damage (61)(62)(63)(64)(65).…”
Section: Ifih1mentioning
confidence: 99%
“…One such gene is Interferon Induced with Helicase C Domain 1 (IFIH1), which encodes an innate immune system receptor for EVs [88]. T1D-associated IFIH1 alleles seem to be associated with enhanced innate immune activation [91]. In addition, the polymorphisms in other innate immune system genes such as tyrosine kinase 2 (TYK2) [92,93] and those regulating the IRF7-driven innate immune system responses are also associated with increased risk of T1D [42,89].…”
Section: Virus-gene Interactionsmentioning
confidence: 99%